Diseño de un sistema fotovoltaico conectado a la red eléctrica para el Bloque A2 de la Facultad de la Energía, las Industrias y los Recursos Naturales no Renovables de la Universidad Nacional de Loja - Rivera Mendoza, Pedro Jair (2024)
This degree work proposes a methodology for designing a photovoltaic system connected to the electricity grid in Ecuador at low voltage (public grid) taking into account the considerations and restrictions established in Regulation ARCERNNR008/23 issued by the Agency for the Regulation and Control of Energy and Non-Renewable Natural Resources for distributed generation for consumers' self-supply of regulated electric power. The main objective is to design the photovoltaic system connected to EERSSA's low-voltage grid according to demand. For this purpose, the worst month methodology was used in the numerical calculation and for its simulation, it is necessary to use the Solarius PV and SketchUp software, which allows its design in 3D respectively. The proposed photovoltaic project has 51 solar panels divided into 4 branches: 3 branches with 13 modules in series each and one branch with 12 modules in series resulting in a total installed power of 28.05 kW. The investment amounts to USD 28,639.44. and it annually produces 39,488.41 kWh to supply the load demand of Block A2 of the Faculty of Energy, Industries and Non-Renewable Natural Resources. Chapter V details the methodological process to establish the number of panels to be used, the orientation and inclination of the panels the determination of electrical protections, the sizing of electrical wiring, and the design of the photovoltaic system. Subsequently, the economic and profitability analysis of the calculated elements is presented. These analyses are, used to determine the feasibility of such a system and to develop the conclusions and recommendations of the work carried out. Keywords: self-supply, photovoltaic, power, demand, orientation.